2009
DOI: 10.1111/j.1467-9450.2008.00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the truth in the details? Extended narratives help distinguishing false “memories” from false “reports”

Abstract: The present study examined the effects of fantasy proneness on false "reports" and false "memories", of existent and non-existent footage of a public event. We predicted that highly fantasy prone individuals would be more likely to stand by their initial claim of having seen a film of the event than low fantasy prone participants when prompted for more details about their experiences. Eighty creative arts students and 80 other students were asked whether they had seen CCTV footage preceding the attack on Swedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…However, whilst it is possible that the reductions in errors in experiments 2 and 3 may have been due entirely to the memory enhancement effects of the combined Focused Meditation/eye-closure technique, other explanations are possible. For example, a variety of evidence suggests that false memory effects can be inflated by demand characteristics and response bias effects (Murray et al 1992;Sjödén et al 2009;Smeets et al 2009;Wagstaff and Frost 1996;Wagstaff et al 2008). In such circumstances, Focused Meditation could be construed as a procedure that changes the contextual demands of the situation facilitating, or "legitimizing", resistance to misleading information and the overturning of previous spurious memory reports.…”
Section: Discussionmentioning
confidence: 97%
“…However, whilst it is possible that the reductions in errors in experiments 2 and 3 may have been due entirely to the memory enhancement effects of the combined Focused Meditation/eye-closure technique, other explanations are possible. For example, a variety of evidence suggests that false memory effects can be inflated by demand characteristics and response bias effects (Murray et al 1992;Sjödén et al 2009;Smeets et al 2009;Wagstaff and Frost 1996;Wagstaff et al 2008). In such circumstances, Focused Meditation could be construed as a procedure that changes the contextual demands of the situation facilitating, or "legitimizing", resistance to misleading information and the overturning of previous spurious memory reports.…”
Section: Discussionmentioning
confidence: 97%
“…Measures have largely relied on a self‐report and on participants' understanding of the difference between belief and memory, but with little systematic follow‐up to confirm the validity of their responses. Given the known difficulty participants have in interpreting questions about memory (Ost et al, 2008; Sjöden, Granhag, Ost, & Roos af Hjelmsäter, 2009; Smeets et al, 2006; Smeets et al, 2009), it would probably be premature to estimate the number of full autobiographical memories and to distinguish these from actual experiences, for example, of eating asparagus or yoghourt. It is interesting that despite these uncertainties, a number of the studies succeeded in bringing about small behavioural changes in their participants, for example, changing the amount of available food consumed in the laboratory (Scoboria, Mazzoni, & Jarry, 2008; Scoboria et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…They suggest that there should be a more formal way of establishing the existence of a personal memory that takes into account the existence of a recollective experience together with confidence in that memory. One way of achieving this as suggested by Ost, Scoboria, Smeets and others (Ost et al, 2008; Sjöden et al, 2009; Smeets et al, 2006; Smeets et al, 2009) is that memory reports are followed up with individual questioning designed to have participants detail their confidence in different elements of their ‘memory’ and to make corresponding source judgements. It would also be valuable to test whether the increased false memory rate produced by personally relevant details is due to the retrieval of additional veridical elements that then find their way into recall of the suggested events or to the retrieval of a true event similar to the one that is being suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Using a sample of Swedish undergraduate students, Sjöden et al (2009) found that women fantasized more than men and art students more than engineering and mathematics students; however, there were no differences in terms of memory distortions between high and low fantasizers.…”
Section: Measuring Individual Differences In Fantasy Pronenessmentioning
confidence: 92%